Computational Analysis of Transposable Elements and CircRNAs in Plants - Oliveira, Liliane Santana; Patera, Andressa Caroline; Domingues, Douglas Silva [UNESP]; Sanches, Danilo Sipoli; Lopes, Fabricio Martins; Bugatti, Pedro Henrique; Saito, Priscila Tiemi Maeda; Maracaja-Coutinho, Vinicius; Durham, Alan Mitchell; Paschoal, Alexandre Rossi (Springer Nature, 2021)
This chapter provides two main contributions: (1) a description of computational tools and databases used to identify and analyze transposable elements (TEs) and circRNAs in plants; and (2) data analysis on public TE and circRNA data. Our goal is to highlight the primary information available in the literature on circular noncoding RNAs and transposable elements in plants. The exploratory analysis performed on publicly available circRNA and TEs data help discuss four sequence features. Finally, we investigate the association on circRNAs:TE in plants in the model organism Arabidopsis thaliana.
Keywords: Bioinformatics; CircRNAs; Circular RNA; Computational methods; Data analysis; Databases; Interaction; Mobile elements; Noncoding; Transposable elements